PHASE STAGES OF CULTURE SHOCK DEPICTED IN THE PICTURE BOOK YOON SERIES - Wulan, Kurnia; Marwinda, Kristin (LINGUAMEDIA Journal, 2024)
The writer analyzes three picture books from the Yoon series by Helen Recorvits andGabi Swiatkowska titled "My Name Is Yoon" (2003), "Yoon And The Christmas Mitten"(2006), and "Yoon And The Jade Bracelet" (2008). This research aims to identify theconflicts that occur in the three picture books. The second element analyzed is todescribe the stages of culture shock experienced by the main character as animmigrant child after moving from Korea to America. This study uses qualitativemethods and a literary sociology approach. Yoon's struggle to adapt in Americafaces various obstacles and challenges full of twists and turns. After overcoming theproblems faced, Yoon eventually becomes a resilient and wise little girl because shecan endure the challenging process of culture shock.